Kewenangan Jaksa Pengacara Negara dalam Memberikan Bantuan Hukum Non Litigasi pada Perkara Perdata: Studi Kasus di Kejaksaan Tinggi DIY - Amara Arruum Acknaasya; Niken Wahyuning Retno Mumpuni (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research aims to examine the authority and role of State Prosecutors in providing non-litigation legal assistance in civil cases, with a case study conducted at the High Prosecutor's Office in Yogyakarta Special Region. The study explores the application of legal rules and analyzes the implementation of legal assistance provided by the Prosecutor's Office in cases of defaulted loans faced by PT. Permodalan Nasional Madani (Persero), a state-owned financial institution supporting SMEs, using both normative and empirical approaches. Primary legal materials such as various related laws and secondary legal materials from journal articles and literature were utilized. The research findings indicate that State Prosecutors significantly influence the provision of non-litigation legal assistance, yet encounter several obstacles. External obstacles include debtors' lack of awareness of their obligations and minimal requests for legal assistance from government agencies, state-owned enterprises, and regional-owned enterprises (BUMD). Meanwhile, internal obstacles primarily relate to budget limitations that hinder the efficiency and effectiveness of handling civil cases. The case highlighted in this study involves the collection of a working capital loan amounting to IDR 45 million provided by PT. PNM Branch Yogyakarta to a debtor who failed to repay. Through case analysis, it was found that State Prosecutors undertook a series of steps from receiving requests for legal assistance, collecting data and evidence, to negotiating and resolving the issue. In this case, negotiations successfully recovered state finances with the debtor settling outstanding debts amounting to IDR 27,925,995. This research underscores the role of State Prosecutors in providing non-litigation legal assistance and emphasizes the need for increased understanding and budget allocation to optimize the resolution of non-litigation civil cases.